Study of tamoxifen associated endometrial changes in women with breast cancer: a prospective study - Coelho, Jyotsna Mirabel; G., Nagarathna; Shet, Dinesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Studies have estimated that women with breast cancer on tamoxifen therapy have a greater risk of developing endometrial cancer. We undertook this study to correlate the ultrasonographic findings, hysteroscopy findings and endometrial pathology in breast cancer patients on tamoxifen. Methods: This was a prospective study conducted over a period of two years. Patients of histologically proven breast cancer on tamoxifen treatment for more than a year were taken into the study. Transvaginal ultrasonography and hysteroscopic biopsy (if endometrial thickness on TVS was 8mm or more) was performed. SPSS software was used for statistical analysis of data. Results: 23 patients had an endometrial thickness between 5-10 mm. 23 between 10.1-15 mm, 13 between 15.1-20 mm and only 1 patient had an ET of more than 20 mm with a mean of 12.27 mm. On Hysteroscopy 24 patients (51%) had a bald endometrium, 14 (29.8%) had hyperplastic endometrium and 9 (19.2%) had polypoid endometrium. On endometrial biopsy, 19 patients had atrophic endometrium, 14 had polypoid endometrium, 11 had non secretory and 7 had secretory endometrium, 1 patient had disordered proliferative endometrium, 1 as hyperplasia without atypia and 1 with complex hyperplasia. 2 were reported as adenocarcinoma. Conclusions: Usage of tamoxifen is warranted in view of its benefits outweighing its risks, the need of a screening program for patients who receive tamoxifen for a prolonged period and the need for a hysteroscopic biopsy when the endometrial thickness is more than 8mm especially in the symptomatic patients.